Achieving Judgment by Means of Forensic Science During the Criminal Proceedings in Romania - Delia Magherescu (Revista Brasileira de Direito Processual Penal)
Achieving the function of judgment by means of forensic science during the criminal proceedings in Romania has presented a real challenge for the judicial system during the years. This challenge must be integrated within the general framework of justice in criminal matters, based primarily on the traditional principles as well as the European ones, such as due process and solving penal cases in reasonable time. The current paper aims to analyze the function of judgment and its achievement through scientific techniques and methods provided by the forensic sciences. Another aim is to consider the penal procedure imperative which leads to ensuring a fair trial. The current paper is part of a research project conducted on the three functions of penal proceedings - accusation, defense and judgment - and their achievement by means of forensic science. The research results state that regarding the function of judgment, its achievement still creates difficulties for judges in their judicial activity of interpreting scientific evidence gathered and examined by the forensic experts. This aspect indicates that there is a lack of understanding the forensic evidence among judges. Despite this deficiency that exists in the judicial activity of solving penal cases and pronouncing decision based on the forensic evidence, it is useful for judges to take into account the forensic science investigation in an inter-professional approach provided by the forensic science. In this context, the forensic experts work in close cooperation with other practitioners, such as legal forensic scientists.